Конвергенція послуг 4G з WI-FI - Кадацька, О. І.; Сабурова, С. А.; Золочевский, О. Р. (ХНУРЕ, 2019)
Researched basic requirements for the convergence of services 4G with Wi-Fi, which lie in the field of security, simplicity and ease of use, high quality and reliability. For simplicity and ease of use, features such as automatic au-thorization and connection, seamless roaming, user management and location monitoring are important. Quality and reliability imply efficient management of a large number (hundreds and thousands) of Wi-Fi access points, mobile traffic unloading (Wi-Fi Offload) and quality of service (QoS) management. At the same time, one of the key condi-tions for convergence lies within the framework of the program-defined network concept (SDN). For example, we are talking about the use of software for centralized management of high-density Wi-Fi networks. This, in particular, makes it possible to implement mechanisms for end-to-end traffic and frequency resource management in convergent Wi-Fi / 4G networks, which can be positioned as one of the key features of the capabilities of smart Wi-Fi networks.
Keywords: LTE; MVNO; 4G; WiFi